Hidrogeochemistry and water quality index from Alto Jacaré-Pepira Watershed (SP), Brazil - Batista, Ludmila Vianna [UNESP]; Gastmans, Didier [UNESP] (Universidade Federal do Rio Grande do Sul, 2015)
Hydrogeochemical studies have been used in order to define chemical reactions produced by water-rock interactions that are responsible to imprint the natural characteristics of surface water, as well as indicate the effects of anthropic activities over water quality, providing information about water availability. Located in Tietê-Jacaré Basin, the Upper Jacaré-Pepira watershed was selected for this study due to its relative geological complexity, to be inserted in an important recharge area of the Guarani Aquifer System (GAS), in which water resources are an important tourist attraction, especially for the city of Brotas (SP). Seventeen river water samples have been collected, in order to determine the Water Quality Index (WQI) as well as evaluate their chemical composition. WQI values vary from 63 to 82, and the water quality classified as “Good”. Electrical conductivity presents strong correlation with total suspended solids and total dissolved solids. The main anion present in water composition is HCO3- showing concentrations varying from 4.12 mg L-1 to 44.50 mg L-1, and Ca2+ and Mg2+ as the main cations, presenting concentrations ranging from 0.38 mg L-1 to 11.60 mg L-1 and 0.55 mg L-1 to 3.20 mg L-1, respectively. Based on chemical composition, river waters were classified as calcium or magnesium bicarbonate type. The overall assessment of the samples indicated the little influence of anthropic activities over water bodies, revealed by WQI values and low concentrations of Cl- e NO3-. Dissolution and weathering of minerals forming rocks and soil from study area are the main geochemical process responsible by final water chemical composition in the Upper Jacaré-Pepira watershed.
Hidrogeoquímica e qualidade das águas superficiais na bacia do Alto Jacaré-Pepira (SP), Brasil
Keywords: Hydrogeochemistry; Jacaré-pepira river; Water quality; Water-rock interaction; WQI